Exploring The Relationship Between Decision-Making Styles and Organizational Performance: A Bibliometric Study - Erina Permata Dewanti; Khusnul Hafifah Farwati; Nabila Anatasya; Aulia Dwi Aminarti; Ellya Gust Priani; Rohana Nur Aini; Muhammad Ramadhani Kesuma (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the intellectual structure and evolution of research on the relationship between decisionmaking styles and organizational performance within the human resource management (HRM) domain, identifying thematic clusters, collaborative networks, and emerging research gaps. A systematic bibliometric analysis was conducted using publication data retrieved from Scopus and the Web of Science Core Collection, spanning the 1990s to the present. VOSviewer was employed to map co-authorship networks, country collaboration patterns, and keyword co-occurrence structures. The analysis reveals that authorship collaboration is clustered into two primary groups, with Hamzah Elrehail functioning as a key bridging node. The United States and the United Kingdom dominate the global collaboration network. Keyword co-occurrence analysis confirms that decision-making styles are closely linked to organizational performance, mediated by strategic, technological, and behavioral factors including artificial intelligence, knowledge management, and intellectual capital. Organizations are advised to adopt flexible, context-sensitive decision-making approaches that combine rational, intuitive, and adaptive styles rather than relying on a single mode, thereby enhancing long-term organizational performance. This study provides a comprehensive bibliometric mapping of two decades of research at the intersection of decision-making styles and organizational performance, identifying underexplored areas including cross-cultural and longitudinal studies, and offers a structured foundation for future empirical work in this domain.